2017
DOI: 10.1002/admi.201601238
|View full text |Cite
|
Sign up to set email alerts
|

Nanocone Decorated ZnO Microspheres Exposing the (0001) Plane and Enhanced Photocatalytic Properties

Abstract: ZnO spherical particles exposing only the (0001) planes are prepared by an established solvothermal method using a water–ethylene glycol (EG) mix as a solvent. It is found that poorly crystalline nanoparticles form first, followed by their aggregation into microspheres consisting of crystallites embedded in EG and precursor molecules/ions. The grown up nanocrystallites and nanocones in the microspheres are all radially aligned. The possible formation mechanisms, in particular, the roles of water molecules, EG,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…A cross section SEM image of a spherulite shown in the inset of Figure a demonstrates a radial arrangement of microrods. The principal driving force of the ordering of the nanocrystallites into such a novel microstructure is probably a dipolar field as discussed in the previous reports on the formation of synthesized vaterite spherulites, naturally occurring aragonite spherulites, synthesized ZnO microspheres. , …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…A cross section SEM image of a spherulite shown in the inset of Figure a demonstrates a radial arrangement of microrods. The principal driving force of the ordering of the nanocrystallites into such a novel microstructure is probably a dipolar field as discussed in the previous reports on the formation of synthesized vaterite spherulites, naturally occurring aragonite spherulites, synthesized ZnO microspheres. , …”
Section: Resultsmentioning
confidence: 95%
“…The principal driving force of the ordering of the nanocrystallites into such a novel microstructure is probably dipolar field as discussed in the previous reports on the formation of synthesized vaterite spherulites, 16 naturally occurring aragonite spherulites, 17 synthesized ZnO microspheres. 27,28 It was noted that when the reaction time was increased to 24 h, the number of rhombohedral crystals significantly increased and the number of the spherulites decreased. The spherulites almost disappeared when the growth time was further increased to 48 h, leaving only rhombohedral crystals.…”
Section: Synthetic Spherulitesmentioning
confidence: 99%
“…Engineering of the surface structure in the micro-or nano-scale to expose a large percentage of {0001} facets has been reported for ZnO. [32][33][34][35] In the present work, the detailed formation processes of both ZnO spherulites and its derivative morphologies including disc decorated microspheres, sea urchin-like, mushroom-like and wood gyro-like microparticles were investigated. For the construction of spherulites, nucleation and development of ZnO nanocrystallites must take place inside a gel like organic substrate.…”
Section: Introductionmentioning
confidence: 93%
“…Theoretical and experimental studies have shown that {0001} facets of ZnO are extraordinarily reactive compared to other crystal facets. Engineering of the surface structure in the micro- or nanoscale to expose a large percentage of {0001} facets has been reported for ZnO. …”
Section: Introductionmentioning
confidence: 99%
“…Even in a more intricate way when the material is of nanometric scale. Engineering the design of porous material in clays is intended to change porosity, surface area 14 , surface content of solids, as well as thermal stability 15 .…”
Section: Porous Materials and Frameworkmentioning
confidence: 99%